Platelet to Lymphocyte Ratio and Neutrophil to Lymphocyte Ratio as Risk Factors for Venous Thrombosis. (July 2018) - Artoni, Andrea; Abbattista, Maria; Bucciarelli, Paolo; Gianniello, Francesca; Scalambrino, Erica; Pappalardo, Emanuela; Peyvandi, Flora; Martinelli, Ida
High platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) are associated with an increased risk of arterial thrombosis, but their role in venous thromboembolism (VTE) has not been fully investigated. A case–control study, of 486 patients with VTE, 100 with cerebral vein thrombosis (CVT), and 299 healthy individuals, was carried out to investigate whether high PLR or NLR values are associated with an increased risk of VTE. Patients with high PLR or NLR did not have an increased risk of VTE (odds ratio [OR] 0.89, 95% confidence interval [CI]: 0.46-1.76; OR: 0.69, 95% CI: 0.34-1.39, respectively) or CVT (OR: 1.65, 95% CI: 0.68-4.00; OR: 0.39, 95% CI: 0.09-1.72, respectively). Subgroups analysis showed that high PLR values were associated with the risk of provoked CVT (OR: 2.65, 95% CI: 1.02-6.92), and there was an interaction with thrombophilia abnormalities (OR: 7.67, 95% CI: 1.67-35.27) in patients with CVT. In conclusion, high PLR and NLR values are not associated with an overall increased risk of VTE or CVT. High PLR values increase the risk of provoked CVT and interact with thrombophilia abnormalities in patients with CVT.